Genetic adaptation of hypermutable pseudomonas aeruginosa colonising the airways of cystic fibrosis patients attending private and public clinics in Gauteng - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2025)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2024.